1984
DOI: 10.2170/jjphysiol.34.747
|View full text |Cite
|
Sign up to set email alerts
|

Influences of glycine and neuron R14 on contraction of the anterior aorta of Aplysia.

Abstract: Firing neuron R14 in the Aplysia parietovisceral ganglion enhances the force of stimulated contractions and causes rhythmic contractions rather than individual contractions in response to a single stimulation of the anterior aorta of Aplysia. Bath application of 1.0 mM glycine to the artery causes a small depolarization, rhythmic contractions and enhances the force of individual, neurally induced contractions of the anterior aorta. These observations suggest that the physiological role of the innervation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…In addition to its role in protein metabolism as the structurally simplest amino acid, glycine also serves as an important and widely distributed inhibitory neurotransmitter in the nervous system of animals from several phyla (Werman et al, 1968; Sawada et al, 1980, 1984; Mladinic et al, 1999 reviewed in Walker and Holden-Dye, 1991; Walker et al, 1996). While its role in adult neurotransmission is relatively well characterized, less is known about glycinergic signaling during development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in protein metabolism as the structurally simplest amino acid, glycine also serves as an important and widely distributed inhibitory neurotransmitter in the nervous system of animals from several phyla (Werman et al, 1968; Sawada et al, 1980, 1984; Mladinic et al, 1999 reviewed in Walker and Holden-Dye, 1991; Walker et al, 1996). While its role in adult neurotransmission is relatively well characterized, less is known about glycinergic signaling during development.…”
Section: Introductionmentioning
confidence: 99%
“…The abdominal ganglion neurons R3-14 are thought to be both glycinergic and peptidergic (35,(41)(42)(43). Our light level immunohistochemical studies demonstrated that these cells send processes into the vascularized connective tissue sheath surrounding the ganglion and connectives, and to the efferent vein of the gill at the base of the heart.…”
Section: The R14 Peptidementioning
confidence: 79%
“…R14 is inhibited by firing of the peptidergic bag cells (Mayeri et al, 1979), an effect that is almost certainly mediated by release of a peptide or peptides into the body fluid rather than at synapses. Considerable evidence points to a role of R14 in the modulation of the control of the Aplysia's circulatory system (Price and McAdoo, 1979;Price et al, 1984;Sawada et al, 1984;Rittenhouse and Price, 1986a, b). Thus, it is possible that the sensitivity of the responses of R14 to external ions, chemical messengers, and amino acids (Ichinose and McAdoo, 1985; are means whereby R14 senses and responds to the state of the organism and participates in the control thereof.…”
Section: Discussionmentioning
confidence: 99%